2011
DOI: 10.1177/0333102411423305
|View full text |Cite
|
Sign up to set email alerts
|

Is cerebrospinal fluid shunting in idiopathic intracranial hypertension worthwhile? A 10-year review

Abstract: We conclude that CSF diversion reduces visual decline and improves visual acuity. Unfortunately, headache remained in the majority of patients and low-pressure headache frequently complicated surgery. Over half of the patients required shunt revision with the majority of these requiring multiple revisions. We suggest that CSF shunting should be conducted as a last resort in those with otherwise untreatable, rapidly declining vision. Alternative treatments, such as weight reduction, may be more effective with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 24 publications
4
110
1
5
Order By: Relevance
“…Although appearing effective in reducing the early ICP-related signs and symptoms, complications included shunt blockage, infection, abdominal and back pain, intracranial hypotension and tonsillar herniation. Shunt revisions were required in 51% with multiple revisions needed in 30% [Sinclair et al 2011].…”
Section: Csf Diversionmentioning
confidence: 99%
“…Although appearing effective in reducing the early ICP-related signs and symptoms, complications included shunt blockage, infection, abdominal and back pain, intracranial hypotension and tonsillar herniation. Shunt revisions were required in 51% with multiple revisions needed in 30% [Sinclair et al 2011].…”
Section: Csf Diversionmentioning
confidence: 99%
“…16 As for the infection and revision rates, previous research has also reported cases of Ն10 revisions per patient in adult PTC shunt groups. 14 In contrast, the highest number of stent procedures recorded for 1 patient was 4.…”
Section: Cost Per 100 Proceduresmentioning
confidence: 94%
“…12,13 The pattern of ongoing shunt complications has also been reported in adult PTC shunt groups, with similarly high revision rates of 51%-63%. 14,15 Furthermore, some "shunt-intolerant" patients can require Ն10 ventriculoperitoneal shunt revisions and Ͼ30 lumboperitoneal shunt revisions. 16 As for the infection and revision rates, previous research has also reported cases of Ն10 revisions per patient in adult PTC shunt groups.…”
Section: Cost Per 100 Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Shunt operation does not provide remission in all patients and may cause surgical complications such as shunt dysfunction and infection. Patients who have benefited from surgery may again become symptomatic in approximately 2 years even though their shunts are functional (50,51,52). In a study by Rosenberg et al (53), the authors found that the mean time to LPe shunt revision was 9 months and that 64% of all LPe shunts were replaced within 6 months in patients with IIH.…”
Section: Treatmentmentioning
confidence: 99%